Fungi and aflatoxin B1 in pre and post fermented sorghum trench type silos destined to bovine intensive-rearing in Brazil - Keller, Luiz Antonio Moura (2012)
The harmful effects of fungi in sorghum silage are an important matter in many countries with hot climates. This culture is very susceptible to fungal contamination and both the storage and processing of this substrate are ideal for the development of fungi there are able to produce mycotoxins. The contamination with mycotoxins, secondary products of the metabolism of certain fungi, that promotes risks to both animal and human health, causes numerous losses for the country. The aim of this study was to identify the toxicogenic fungi present in sorghum silage for beef cattle consumption and determine the occurrence of aflatoxin B1 (AFB1) in the same substrate. A total of 60 pre-fermented and 60 post-fermented samples of sorghum silage were analyzed. Total fungal counts and natural incidence of toxigenic Aspergillus, Penicillium y Fusarium species were performed on dichloran rose bengal chloranphenicol agar, dichloran glycerol agar 18 % and Nash-Snyder culture media. Aflatoxin B1 contamination was determined using high pressure liquid chromatography (HPLC). About 30 % of samples from pre-fermented sorghum and 55 % of post-fermented samples were above the recommended limits (1.0 x 104 CFU g-1). The most frequent fungal species in both types of sorghum samples were A. flavus, P. citrinum, P. islandicum and F. verticillioides. An average of 32 % samples, pre and post-fermented, were positive for AFB1. The presence of fungi and AFB1 in the feedstuffs indicates contamination. This toxin could affect animal productivity and health. This fact requires periodic monitoring to prevent the occurrence of mycotoxicosis in animal production.